Effect of cooking posture on birth weight - Yugantara R Kadam; Pragati V Chavan; Randheer V Dhoble; Alka D Gore (Wolters Kluwer Medknow Publications, 2014)
Background: Low birth weight is still prevalent and has a multifactorial causation. Indian women in the reproductive age group, usually engage themselves and spend considerable time in cooking. Cooking, when done in a standing position may affect birth weight adversely. Aim and Objective: The goal of this study was to study the postnatal mothers and their newborns to assess the effect of cooking posture on birth weight. Materials and Methods: Study type-cross-sectional study setting: Hospital based. Sample size: 499, study subject: Mothers and their newborns. Inclusion criteria: Those mothers, who are using liquid petroleum gas for cooking, attended ANC Clinic from the first trimester with minimum three antenatal visits, non-anemic at the end of the second trimester, full term and singleton delivery. Exclusion criteria: Those mothers with a history of toxemias of pregnancy, diabetes, tuberculosis etc., delivered pre-term and tobacco chewers. Study period: July 2011 to December 2011, study tools: (i) Questionnaire. (ii) Pediatric weighing machine. Statistical Analysis: Percentages, mean and standard deviation of birth weight, χ2 -test, ANOVA, Z-test. Results: Babies born to mothers cooking in a standing position were 101 g lighter than those born to mothers cooking in a sitting position. Observed difference was significant (z = 2.220, P = 0.027). Multivariate analysis shows significant association between cooking posture and birth weight (P = 0.034). There was a low degree but significant negative correlation between duration of cooking and birth weight in a standing position (r = −0.115, P = 0.045). Conclusion: Cooking posture affects birth weight adversely which is preventable as it is a modifiable risk factor.